Associations between baseline opioid use disorder severity, mental health and biopsychosocial functioning, with clinical responses to computer-assisted therapy treatment. (4th May 2021) - Elison-Davies, Sarah; Märtens, Kaspar; Yau, Christopher; Davies, Glyn; Ward, Jonathan
ABSTRACT: Background : Increasing rates of opioid-related overdose have been identified globally. Treatment for opioid use disorders (OUD) includes medications for opioid use disorder (MOUD) alongside behavioral support. Novel approaches to behavioral support should be explored, including computer-assisted therapy (CAT) programs. Objectives : Examine differences between baseline and post-treatment measures of opioid use and biopsychosocial functioning for individuals with OUD engaging with the CAT program 'Breaking Free Online, ' and the extent to which participant characteristics may be associated with post-treatment measures. Methods : 1107 individuals engaged with CAT and provided baseline and post-treatment data – 724 (65.4%) were male, 383 (34.6%) were female. Results : Significant differences between baseline and post-treatment measures were identified (all p <.0001, effect sizes range:15 –.50). Participant characteristics were associated with post-treatment measures of opioid use, opioid dependence, mental health issues, quality of life, and biopsychosocial impairment (all p <.0001). An aggregated consensus measure of clinical impairment was found to be associated with changes in opioid use and post-treatment biopsychosocial functioning measures, with those participants with greater baseline clinical impairment demonstrating a greater magnitude of improvement from baseline to post-treatment than those with lower clinical impairment. Conclusion : CAT may reduce opioid use and improve biopsychosocial functioning in individuals with OUD. CAT could therefore provide a solution to the global opioid crisis if delivered as combination behavioral support alongside MOUD. Findings also indicate that it may be important for treatment systems to identify individuals with psychosocial complexity who might require behavioral support and MOUD.